Interventional stroke treatment – Is it also safe for arteries? Looking at thrombectomy wall damage through clot histology. Issue 3 (June 2021) - Donnerstag, Frank; Götz, Friedrich; Dadak, Mete; Raab, Peter; Iglesias, Enrico Calvino; Werlein, Christopher; Lanfermann, Heinrich; Jonigk, Danny
Background and purpose: The aim of this study was to investigate whether morphological evidence of intracranial vascular injury can be found in the occluding thrombi of patients with ischemic stroke. Methods: From 2015 until 2018 specimens of thrombi from patients with large vessel occlusion treated either by stent-assisted aspiration thrombectomy (TE) or by aspiration thrombectomy were prospectively collected. Thrombus specimens were formalin-fixed, paraffin-embedded and stained. Architectural features, presence of parts of vessel wall or atheromatous material, organisation of the thrombi, technique and number of thrombectomy manoeuvers were evaluated. Results: Thrombus specimens from 302 patients were analyzed. 238 (80%) patients were treated with stent-assisted aspiration TE and 64 (20%) patients with aspiration TE only. 286 (95%) had fresh thrombi, 14 (4.6%) showed initial/complete thrombus organisation and multi-staged thrombi were found in 2 (<1%) patients. In 8 patients (2.6%) we found atypical thrombus content after a time interval longer 6 hours after onset and final thrombectomy manoeuvre: 4 with atheromatous material and 4 with parts of a vessel wall. In 1 patient with parts of vessel wall angiographically a dissection was detected. No parts of the vessel wall were found after sole aspiration thrombectomy. Conclusions: The overall risk of arterial vessel wall injury aspiration thrombectomy was low in our study. Aspiration thrombectomy and the procedure related with a retrieving device together with an ischemia time longer than 6 hours may increase the risk of vessel injury through the thrombectomy procedure. Further investigations are necessary to elucidate the influence of the mentioned aspects.